The Etiology, Pathogenesis, and Pathological Anatomy of Diffuse Alveolar Lesion - A. L. Chernyaev; M. V. Samsonova (Общая реаниматология, 2005)
The paper considers the current concept of diffuse alveolar lesion (DAL), a rather rare condition that requires intensive care measures. The clinicomorphological manifestation of DAL is adult respiratory distress syndrome. The causes of DAL occurring with an infectious process, including septic conditions, as well as with inhalations of toxic gases and aerosols; shock, radiation, drug therapy, etc. are presented. The pathogenesis of DAL and its pathological anatomy is described in detail, pathological lung alterations in different periods after the onset of the disease being characterized.